Investigation of Solidification and Segregation Characteristics of Cast Ni-Base Superalloy K417G. Issue 3 (March 2018) - Gong, Li; Chen, Bo; Du, Zhanhui; Zhang, Mengshu; Liu, Ruichang; Liu, Kui
Graphical Abstract: Highlights: The liquidus of K417G superalloy is 1345 °C, and the solidus is 1270 °C. L ↧ γ at 1345 °C; L ↧ γ + M C at 1330 °C; L ↧ γ + γ′ at 1300 °C; γ ↧ γ′ at 1215 °C. DSC, isothermal solidification experiment and Thermo-Calc were used together. Al accumulated to liquid at the initial stage, but gathered into solid later. Line scanning was used to analyze elemental distribution in γ, γγ′ and liquid. Abstract : Differential scanning calorimetry (DSC) analysis, isothermal solidification experiment and Thermo-Calc simulation were employed to investigate solidification characteristics of K417G Ni-base superalloy. Electron probe microanalysis (EPMA) was employed to analyze the segregation characteristics. Liquidus, solidus and the formation temperatures of main phases were measured. In the process of solidification, the volume fraction of liquid dropped dramatically in the initial stage, while the dropping rate became very low in the final stage due to severe segregation of positive segregation elements into the residual liquid. The solidification began with the formation of primary γ. Then with solidification proceeding, Ti and Mo were enriched in the liquid interdendrite, which resulted in the precipitation of M C carbides in the interdendrite. Al accumulated into liquid at the initial stage, but gathered to solid later due to the precipitation of γ/γ′ eutectic at the intermediate stage of solidification. However, Co tended to segregate toward the solid phase. In the case of K417G alloy, combining DSC analysis and isothermal solidification experiment is a good way to investigate the solidification characteristics. Thermo-Calc simulation can serve as reference to investigate K417G alloy.